Structure and quantification of Ce3+/Ce4+ and stability analysis of basaltic glasses for the immobilization of simulated tetravalent amines - Qin Tong; Song Liu; Jun Liang; Qi Zhang; Meiying Liao (Scientific Reports)
Abstract Basaltic glass was prepared via the solid-state melt method, using Ce4+ to simulate tetravalent actinides. The structure, thermal stability and leaching characteristics of basaltic glass with different contents of CeO2 were investigated. The XRD/SEM-EDX/Raman results showed that the simulated waste loading of CeO2 in basaltic glass reached ~ 18 wt%, and CeO2 crystals precipitated when the CeO2 content reached 20 wt%. XPS analysis revealed that approximately half of the Ce4+ ions in the basaltic glass doped with CeO2 were reduced to Ce3+ ions. The DSC results showed that the thermal stability increased with increasing CeO2 content. The ASTM product consistency test (PCT) results indicated that all the samples had good leaching resistance. Among them, the standard mass loss of Ce was the greatest after 28 days: The NL Ce was 2 orders of magnitude lower than those of the other elements.